Customer Focus Berbasis Total Quality Management (TQM) di SMA Muhammadiyah 1 Taman - Darmawan, Diki; Prasietyawan, Ruben Diaz; Hazin, Mufarrihul; Murtadlo, Murtadlo; Cindy, Agustin Hanivia (FKIP Universitas Muhammadiyah Sukabumi, 2024)
In the world of education, Total Quality Management (TQM) is the main weapon in improving the overall quality of education. One of the principles of Total Quality Management (TQM) is customer satisfaction. Customer satisfaction is the most important priority in an organization, so organizations must focus on customers. The purpose of this research is to find out how SMA Muhammadiyah 1 Taman satisfies customers. This research uses a qualitative approach with data collection methods using interviews with the director of SMA Muhammadiyah 1 Taman. Based on the results of research that has been carried out, SMA Muhammadiyah 1 Taman has a very good way of implementing Total Quality Management (TQM) based on customer satisfaction. This is proven by the fact that SMA Muhammadiyah 1 Taman really minimizes free hours in subjects. SMA Muhammadiyah 1 Taman also facilitates students to study outside of class hours with their teaching staff in preparation for taking part in Olympics or competitions. In cultivating discipline, teaching staff and educational staff display behavior that shows a disciplined attitude towards time. When accepting new students (PPDB) at the initial stage, accepted students will be given a psychological test first. This is aimed at understanding the needs of students. Apart from that, SMA Muhammadiyah 1 Taman public relations always conveys information quickly when there is new news, policies and regulations.